Pengembangan Media Pembelajaran IPA-Biologi Berbasis Visual Basic untuk Siswa Kelas VIII SMP Negeri 42 Kepulauan Selayar - Fatmawati, Fatmawati; Hala, Yusminah; Arsyad, Muhammad (UNM Journal of Biological Education, 2023)
learning media and describe the quality of the media based on aspects of validity, practicality, and effectiveness. This study employed the type of R&D (Research and Development) research with the ADDIE development model which consisted of 5 stages, namely analysis, design, development, implementation, and evaluation. The respondents of the product trial were students of grade VIII at SMPN 42 Selayar Islands 7 students. The results of the study indicate that the assessment by material and media experts obtain an average score of 4.4 with valid criteria, so the media developed is declared valid. The results of the questionnaire data analysis of students’ responses to the media obtain an average score of 93.5 with very strong criteria and the teacher's response to the media obtain an average score of 86.6 with very strong criteria. The results of the observation on the implementation of learning reveal that the classification is very good with the percentage reaching 92.85%, so the media is declared as practical. The percentage of classical completeness of the learning outcomes test achieves 85.7%, so the media is declared as effective. Based on the results of the aforementioned data analysis, it can be concluded that the science-biology learning media based on visual basic on the Motion System material in Humans can be applied in learning activities.